Réformes territoriales et modifications des rapports ville-montagne dans les Alpes-Maritimes - Lauranne Jacob (Revue de Géographie Alpine)
The objective of this paper is to present a case study specific to the Alpes-Maritimes département; a region of France characterised by its dual maritime and alpine nature, and one that has undergone significant territorial restructuring susceptible to alter relationships between urban and mountainous regions.Almost four years after territorial reforms were implemented, analysis of new territorial divisions, informed by historical, political and sociological aspects, suggests that they have not, for the time being, resulted in radical changes to the current balance between urban and mountainous regions in the Alpes-Maritimes département. The creation of large coastal and alpine intermunicipal authorities signifies that links between urban and mountainous regions need to be addressed in order to ensure they complement each other.However, development policy for mountainous regions could result in a form of ‘disneyfication’ (Crettaz 1993) in mountainous regions.